The social role of pediatrics in the past and present times - Gregorio Serra; Mario Giuffrè; Ettore Piro; Giovanni Corsello (BMC, 2021)
Abstract Pediatrics and society are closely related. This link is as old as the history of Pediatrics, and dates to the second half of the eighteenth century. The vocation of the first European pediatric schools, indeed, was clinical and scientific, as well as social. The founding fathers of Pediatrics were scientists of great talent, and many of them benefactors and philanthropists. They spent their lives assisting the suffering childhood, and became promoters and organizers of social securities for the poorest and most vulnerable categories. The attention to the problems of abandonment was closely linked to study, prevention, and treatment of pathologies (especially infectious, deficiency and neurological ones). The profile and activity of pediatricians grew in the following decades after the birth of the first pediatric schools. The University institutions contributed to provide a further impulse to childcare as well as cultural authority, also thanks to the foundation of the first chairs and scientific journals of Pediatrics. The relevance and prestige of the studies performed rapidly spread throughout Europe, and also reached our country, contributing to a progressive and relevant improvement in the quality of children's care, and in the meantime to the decrease of neonatal and infant mortality rates. Today's pediatricians, as in the past, must spend his efforts to face the needs of children and their families, be their social receptor, interpreter if necessary, and credible and authoritative interlocutor beside institutions. The current coronavirus pandemic dramatically exposed social inequalities and inequities. In this new scenario, the pediatrician's role of defender of all children becomes even more necessary and indispensable. Here we trace the historical steps which led to the birth and development of pediatrics, as independent medical discipline with ethical and social vocation. Its rise within the University institutions is analyzed, as well as the contribution of the greatest European and Italian masters. Finally, the role of today's pediatrician is described, his responsibilities also in dealing with new health critical issues, related to the biological, cultural, and psychological changes of the patients of present days. He must have holistic competences, to effectively take care of all children. In addition, he must socially act to guarantee the best possible context for the well-being of the child.